The Gnostic Paradigm - Elias, N. author. aut Link
XV, 191 p.
Keywords: No study has been carried out examining the gnostic undercurrents in medieval England. For the first time, Natanela Elias investigates the existence of these gnostic traces, using prominent late medieval English literary works such as Piers Plowman and Confessio Amantis and ultimately shedding light on a previously overlooked religious dimension.